Mesenchymal Stromal Cell-Based Therapies for Chronic Lung Disease of Prematurity - Strueby, Lannae; Thébaud, Bernard (American Journal of Perinatology, 2016)
Advances in perinatal care allow the survival of ever more premature infants. By approaching the biological limit of viability, survival free of injury becomes more challenging. As a consequence, bronchopulmonary dysplasia (BPD), the chronic lung disease of prematurity, remains one of the main complications in infants born before 28 weeks' gestation. Currently, there is no treatment for BPD. Recent progress in understanding the biology of stem cells has opened unprecedented therapeutic options to mitigate lung injury and promote lung growth. Perinatal tissue, such as the umbilical cord and the placenta, represents a rich source of potent repair cells. Thus far, mesenchymal stromal cell (MSC)-based therapies demonstrate the most potential for protecting the developing lung from injury. Preclinical evidence supporting this potential therapeutic role has provided the basis for the initiation of phase I and II clinical trials in preterm neonates. This brief review summarizes the current knowledge accumulated over the past 10 years about MSCs and their repair potential in BPD.
Keywords: newborn; lung injury; inflammation; bronchopulmonary dysplasia; stem cells; regenerative medicine; prematurity